Journal of the Australian Early Medieval Association (Australian Early Medieval Association, 2005)
This journal is a double-blind peer reviewed journal. It publishes articles, reviews and short notes relating to all aspects of the early medieval period from late antiquity and the end of the Roman empire to about the end of the eleventh century.